Monitoring environmental and climate goals for European agriculture: User perspectives on the optimization of the Copernicus evolution offer. (15th October 2021) - Schiavon, Emma; Taramelli, Andrea; Tornato, Antonella; Pierangeli, Fabio
Abstract: A vicious cycle exists between agricultural production and climate change, where agriculture is both a driver and a victim of the changing climate. While new and ambitious environmental and climate change-oriented goals are being introduced in Europe, the monitoring of these objectives is often jeopardized by a lack of technological means and a reliance on heavy administrative procedures. In particular, remote sensing technologies have the potential to significantly improve the monitoring of such goals but the characteristics of such missions should take into consideration the needs of users to guarantee return on investments and effective policy implementation. This study aims at identifying gaps in the current offer of Copernicus products for the monitoring of the agricultural sector through the elicitation of stakeholder requirements. The methodology is applied to the case study of Italy while the approach is scalable at European level. The elicitation process associates user needs to the European and national legislative framework to create a policy-oriented demand of Copernicus Earth Observation services. Results show the limitations faced by environmental managers in relation to the use of Remote Sensing technologies and the shortcomings associated with a purely technology driven approach to the development of satellite missions. Through the introduction of this flexible and user centred approach instead, this paper provides a clear overview of agro-environmental user requirements and represents the basis for the definition of an integrated agricultural service. Highlights: Eliciting user requirements provides guidance for the improvement of the offer of European Earth Observation products. The methodology used improves the institutional market pull for the development of the EO upstream offer Aligning technological development to operational needs can enhance agro-environmental and climate goals. Investing in synergies between missions can improve the implementation of the Common Agricultural Policy post 2020.